A Man Called Brian - Shoolizadeh, Mahmoud (United Kingdom, 2005)
The film introduces 55 year-old Briton called Brian Haw who has staged a 24-hour sit-in opposite the Houses of Parliament in London for over five years in protest against the invasion of US and British military forces of Iraq and Afghanistan.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films